HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG HIPERBILIRUBIN DENGAN SIKAP DAN PERILAKU MENJEMUR BAYI DI KELURAHAN SANGKRAH - Rahayu Setyaningsih; Ersa Trianingsih (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractInterviews with mother who have babies aged 0-6 months in the Village Sangkrah, founddifferent maternal understanding of hiperbilirubin, some of mothers not understand abouthiperbilirubin, its causes and how to prevent it. The attitude of the mothers also variessome wants sunning their babies every morning whereas plenty were reluctant becausethey do not know of its benefits. The purpose of the study: to determine the correlation ofmother's level of knowledge about hiperbilirubin with attitudes and behavior sunning babyThe subjects were all mothers with babies 0-6 months in the Village Sangkrah as manyas 45 people. This research method of bivariate analysis using Spearman Rank,multivariate analysis with Pearson Correlation to find the correlation of three variables: thelevel of knowledge of mothers about hiperbilirubin with attitudes and behavior in infantssunning.The results of the bivariate analysis using Spearman Rank with Î± = 5% (0.05) wasobtained p <0.001 to p <0.05, which means that the hypothesis is accepted, there is acorrelation the level of knowledge about hiperbilirubin with the attitudes and behaviorsunning baby in village Sangkrah. Multivariate statistical test using Pearson Correlation Î±= 5% (0.05) was obtained p <0.001 for the correlation between knowledge with attitude,either correlation knowledge with behavioral or correlation between attitudes withbehavioral earn p <0.05. The correlation coefficient ranged from 0.541 to 0.583 whichshows the strength of the relationship in the medium category.Keywords: Knowledge, Attitude, Behavior, Hiperbilirubin, Sunning Baby